2019
DOI: 10.18697/ajfand.87.18355
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of climate-smart DroughtTEGO® varieties in Kenya

Abstract: to address the impact of drought occasioned by climate change. To determine the level of adoption and use of DroughtTEGO ® maize hybrids in Kenya, a survey was conducted involving 642 farming households from six counties. The results indicated a high rate of awareness of at least one of the DroughtTEGO ® varieties (61%). The adoption rate stood at 26% with WE1101 maize hybrid being the most widely known and adopted due to its availability and high yields. Expected adoption was calculated at 89% with about 65% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…This hybrid has a medium maturity period (120 d) in most of the agroecologies across Kenya. Muinga et al (2019) reported that the adoption rate of DroughtTEGO hybrids was 26%, after only 3 yr of introduction to smallholder farmers in Kenya. In addition, the study showed that 62% of the farmers interviewed were aware of at least one DroughtTEGO hybrid and that 42% of them were considering purchasing WE1101 DroughtTEGO hybrid seed for planting.…”
Section: Resultsmentioning
confidence: 99%
“…This hybrid has a medium maturity period (120 d) in most of the agroecologies across Kenya. Muinga et al (2019) reported that the adoption rate of DroughtTEGO hybrids was 26%, after only 3 yr of introduction to smallholder farmers in Kenya. In addition, the study showed that 62% of the farmers interviewed were aware of at least one DroughtTEGO hybrid and that 42% of them were considering purchasing WE1101 DroughtTEGO hybrid seed for planting.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for the non-poor and the poor citizens in most rural setups, agriculture continues to be the main source of livelihood. Similar to this, the agricultural industry has been the major employer in Kenya, contributing to 35% of the nation's GDP in the year 2020, which is one of the highest percentages in African nations (Muinga et al, 2019). This therefore makes it important to determine the connection between agricultural growth and external debt.…”
Section: Introductionmentioning
confidence: 87%
“…This allows farmers to see the varieties in action and learn about their benefits firsthand. The main barriers to adopting DroughtTEGO® varieties are a lack of information about their productivity, unavailability of seed when needed, and the high cost compared to other locally available varieties [17,18]. Oniang'o et al [18] found that well-thought-out strategies to influence awareness and adoption of drought-tolerant maize include strengthening extension services, providing credit to small-scale farmers, investigating cases of discontinued use, improving access to seed through agro-dealerships, targeting age and gender, and specific agro-ecological zones.…”
Section: Drought-tolerant Maize Varietiesmentioning
confidence: 99%